Decomposing the complexity of heart-rate variability by the multifractal–multiscale approach to detrended fluctuation analysis: an application to low-level spinal cord injury. (30th August 2019) - Castiglioni, Paolo; Merati, Giampiero; Parati, Gianfranco; Faini, Andrea
Abstract: Objective : While several studies have assessed autonomic cardiovascular control after a spinal cord lesion using heart-rate variability (HRV) indices in the frequency and time domains, complexity measures have rarely been used, even if detrended fluctuation analysis (DFA) appeared promising. Recent developments in DFA decompose the multifractal contributions using temporal scales. Our aim is to evaluate the potential of these new DFA tools, considering as an example application the decomposition of HRV complexity in individuals with spinal cord injury (SCI) at a low lesion level, for whom alterations in traditional indices are not expected. Approach : We enrolled 14 subjects with SCI with a lesion below the eleventh thoracic vertebra and 34 able-bodied (AB) controls. We recorded the R–R intervals (RRI) for 10 min in supine and sitting postures. We applied the multifractal–multiscale (MFMS) DFA to derive scale coefficients, α ( q, τ ), with function of the multifractal order q and scale τ, and evaluated a scale-coefficient dispersion index, α SD ( τ ), as the standard deviation of α ( q, τ ) over q . We calculated the RRI increments, their magnitude and sign, estimating the MFMS DFA coefficients for the series of magnitude α m ( q, τ ) and sign α s ( q, τ ). Main results : While sitting, differences between SCI and AB groups depended on q for coefficients 16  <   τ   <  32 s, so that α SD ( τ ) was lower in individuals with SCI at τ   =  25 s. In the supine condition, short-term scales were greater in individuals with SCI for all q, and α SD ( τ ) did not differ between groups. Group differences were found in α s ( q, τ ) and not in α m ( q, τ ) or in traditional HRV indices. The surrogate analysis showed AB–SCI differences in linear HRV components at scales τ   <  16 s and nonlinear components at larger scales. Significance : Complexity decomposition by DFA describes autonomic alterations in HRV in low-level paraplegia better than traditional indices, probably pointing out a loss of system complexity in the sitting posture and an impaired sympatho/vagal modulation in the supine position.